Reexamination of magnetic isotope and field effects on adenosine triphosphate production by creatine kinase - COEY, JOHN MICHAEL DAVID; PRINA MELLO, ADRIELE (My University, 2012)
The influence of isotopically enriched magnesium on the creatine kinase catalyzed phosphorylation of adenosine diphosphate is examined in two independent series of experiments where adenosine triphosphate (ATP) concentrations were determined by a luciferase-linked luminescence end-point assay or a real-time spectrophotometric assay. No increase was observed between the rates of ATP production with natural Mg, (24)Mg, and (25)Mg, nor was any significant magnetic field effect observed in magnetic fields from 3 to 1,000 mT. Our results are in conflict with those reported by Buchachenko et al. [J Am Chem Soc 130:12868-12869 (2008)], and they challenge these authors' general claims that a large (two- to threefold) magnetic isotope effect is "universally observable" for ATP-producing enzymes [Her Russ Acad Sci 80:22-28 (2010)] and that "enzymatic phosphorylation is an ion-radical, electron-spin-selective process" [Proc Natl Acad Sci USA 101:10793-10796 (2005)].
PUBLISHED
Keywords: Physics